A Musical Composer's Interpretation of Sacred Text. Issue 2 (25th November 2022) - DeWitt, Peter B; DeWitt, Patricia A
Abstract : When a composer in the Western music tradition of the last 500 years sets a text to music, they make certain choices about that relationship, which may depend on their emotional reaction to the text or to their pictorial perception of it. Emotional and pictorial linkages between music and sacred text are described in two examples, one a musical setting of a Christian liturgy, and one a variation set on a Christian folk hymn in which the variations draw on the texts of successive stanzas. These linkages are part of an extensive history of usage of devices by which a composer responds to textual inspiration. Because of the centuries during which associations between music and text have been developed in the minds of composers, performers and listeners of Western countries, the music can become an enhancement of, or even a substitute for, elements present in the text.